BRAINWASHING SCHEMES AMONG ADOLESCENTS WITH RADICAL POTENTIAL THROUGH STUDENT ORGANIZATIONS IN HIGHER EDUCATION INSTITUTIONS - Wahyu Kurniawan (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study aims to examine the psychological aspects of brainwashing schemes among adolescents with radical potential within student organizations at University X. Adolescence is a period of contradictions, where psychological stability is often fragile, and emotions can be difficult to control. This instability can lead to behaviors that undermine national unity, as evidenced by the growing tendency of youth toward religious radicalism. According to data from Babel Review (2019), based on a 2017 survey by the National Counterterrorism Agency (BNPT), the Bangka Belitung Islands Province ranks fifth nationally in radicalism potential within educational settings. The rise of religious radicalism is often rooted in fragmented religious understanding, misinterpretation of religious texts, and political and economic deprivation, as noted by Azyumardi Azra. This study employs a qualitative methodology to explore the internal cadre training processes within radical organizations, particularly focusing on the brainwashing techniques used in recruiting new members. The findings reveal that these brainwashing practices are systematically and structurally implemented within such organizations, posing a serious threat to social harmony and national unity. This research contributes to a deeper understanding of the radicalization process among adolescents and provides insights into more effective preventive strategies through educational and psychological interventions.